Development of Hydrogen Fuel Production as a Prospect for Establishing Technological Competitive Advantages of Russia; Innovation Management and Education Excellence Vision 2020: from Regional Development Sustainability to Global Economic Growth - Boretsky E. A. Evgeny Aleksandrovich; Egorova M. S. Mariya Sergeevna; Filippova T. V. Tatiana Vasilievna; Chesnokova I. A. Irina Anatolievna (2016, 2016)
Title screen